The evolving role of national central banks - V. V. Kuznetsova; O. I. larina (Финансы: теория и практика)
The article is devoted to the study of modern trends in the development of functions and instruments of central banks (CB). The article aims to identify new CB approaches to crisis management and the used tools’ analysis and to study the transformation of CB activities and their current role. The authors use general scientific and special research methods, including comparative legal analysis and the method of systematization. The article focuses on the current international discussion on the evolving role of CB, provides an overview of experts’ opinions on issues related to assessing how CB activities influenced the formation and development of the 2007 global financial crisis. The spread of the latest crisis caused by the COVID-19 pandemic was different from the spread of the 2007 crisis when financial markets were first hit and then stress spread to the real economy through reduced confidence and tightening credit conditions for businesses and households. The authors note that the pandemic crisis developed differently: first, the real economy was affected, which was accompanied by a fall in GDP, and then conditions in the financial sector worsened. The authors systematized the CB measures in response to the pandemic and analyzed them by groups of countries: the CB measures of the advanced economies and countries with emerging markets were broadly similar. Based on a comparative analysis of the monetary instruments, the authors conclude that the advanced economies CBs have extremely limited opportunities to use interest rates to manage the crisis, while the emerging markets CBs still have some space for their regulation. The paper also analyses other CB instruments used during the crisis caused by the pandemic. The authors note that the measures implemented by CBs reflect their increased role in modern economic systems and the change in the long-known traditional functions. This research may be useful to state bodies in the implementation and coordination of the policy in the field of regulation of CB activities.